Broadband wavelength tuning of electrically stretchable chiral photonic gel - Nam Seungmin; Wang Dahee; Lee Gyubin; Choi Su Seok (Nanophotonics, 2022)
Chiral photonic-band structure provides technical benefits in the form of a self-assembled helical structure and further functional wavelength tunability that exploits helical deformation according to pitch changes. The stopband wavelength control of the chiral photonic-band structure can be obtained by individual electrical methods or mechanical stretching deformation approaches. However, research on combined electric control of stretchable chiral photonic-band wavelength control while ensuring optical stability during the tuning process has remained limited till now. In this study, using the hybrid structure of elastomeric mesogenic chiral photonic gels (CPGs) with an electrically controlled dielectric soft actuator, we report the first observation of electrically stretchable CPGs and their electro-mechano-optical behaviors. The reliable wavelength tuning of a CPG to a broadband wavelength of ∼171 nm changed with high optical stability and repeated wavelength transitions of up to 100 times. Accordingly, for the first time, electrical wavelength tuning method of stretchable chiral liquid crystal photonicband structure was investigated.